Injectable Ca2 +-tannic acid loaded nano composite material as well as preparation method and application thereof
By developing an injectable nanocomposite material loaded with Ca2+-tannin (CaTA@Gel), a dual network hydrogel is constructed using Ca2+-algin sodium alginate ion cross-linking and PEG-SS4 free radical polymerization, the problem of periodontitis treatment is solved, and the long-term retention and continuous release of the material in the periodontaneous pocket is achieved, which significantly improves the effect of periodontaneous treatment.
Patent Information
- Application Number
- CN202411799747.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Existing treatment methods for periodontitis are difficult to completely eradicate deep infections and reverse the inflammatory environment, and the retention time of active nanocomposites in periodontal pockets is short and the treatment effect is limited.
A single injectable nanocomposite material loaded with Ca2+-tannin (CaTA@Gel) was developed to construct a dual network hydrogel through Ca2+-sodium alginate ion cross-linking and PEG-SS4 radical polymerization to ensure long-term retention of the material in the periodontal pocket and continuous release of CaTA.
Long-term retention and continuous release in the periodontal pocket are achieved, which significantly inhibits bacteria, removes reactive oxygen species, promotes alveolar bone regeneration, and improves the effect of periodontitis treatment.
Smart Images

Figure CN119606864A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oral medical materials, and more particularly to an injectable loaded Ca 2+ -Nanocomposite material of tannic acid and its preparation method and application. Background Art
[0002] As an infectious and chronic inflammatory disease, periodontitis may be caused by many bad habits, such as incomplete teeth cleaning and excessive consumption of high-sugar foods. It not only causes redness and swelling of the gums, but also causes alveolar bone defects, which may eventually lead to tooth loss, thereby limiting oral activities such as speaking and chewing. In addition, periodontitis is also associated with systemic diseases, which seriously affects the quality of life of patients. According to many reports, excessive oxidative stress breaks the balance between reactive oxygen species (ROS) and antioxidant stress and is the main cause of disease onset. In addition, bacteria and lipopolysaccharide (LPS) activate macrophages and neutrophils, enhance the production of reactive oxygen species, and osteoclasts are awakened and secrete matrix metalloproteinases (MMPs) to damage periodontal attachment. Therefore, inhibiting bacteria, regulating reactive oxygen species and promoting osteogenesis in the local environment have great scientific and clinical significance for the treatment of periodontitis.
[0003] At present, clinical treatments for periodontitis include local debridement, root planing and drug therapy. These methods can temporarily alleviate the development of periodontal disease. However, it is still a huge challenge to completely eradicate deep infection and reverse the inflammatory environment, not to mention alveolar bone regeneration. Based on the above shortcomings, biomaterials with drug delivery and tissue engineering functions provide a new perspective for the treatment of periodontitis. Active nanocomposites containing cerium dioxide, manganese tetraoxide and metal-phenol networks show excellent ability to remove excess reactive oxygen species in inflammation and relieve hypoxia in mimicking antioxidant enzyme activity. Therefore, it is often used in the fields of cell protection, anti-inflammatory and cancer treatment. As a result, people have focused on the application of active nanocomposites in the treatment of periodontitis. However, there are still some limitations of active nanocomposites in their application that cannot be ignored, such as their rapid clearance by saliva due to the dynamic microenvironment in the periodontal pocket. Injectable hydrogels provide a biocompatible and practical matrix for the delivery of nanocomposites and the extension of the working cycle. In addition, the nanocomposites in the hydrogel are not only a bioactive component, but also part of the hydrogel network to prolong the retention time at the lesion site.
[0004] However, simple mixing of hydrogels and nanocomposites may still lead to bursting, i.e., the sudden release of nanocomposites, resulting in limited therapeutic outcomes. At the same time, most active nanocomposites only perform relatively simple functions and cannot meet the requirements of anti-inflammatory and osteogenesis in periodontitis treatment.
[0005] Therefore, it is of great significance to develop bioactive injectable hydrogels with multiple functions such as antibacterial, anti-inflammatory and osteogenic properties for the treatment of periodontitis. Summary of the invention
[0006] In view of this, the present invention provides an injectable Ca-carrying 2+ -Tannin acid nanocomposite (CaTA@Gel) for the treatment of periodontitis, in which TA has an inhibitory effect on bacteria and inflammation and Ca 2+ The osteogenic effect of CaTA bioactive nanocomposites not only has antibacterial, ROS-scavenging and osteogenesis-promoting effects, but is also an indispensable part of constructing double-network hydrogels.
[0007] One of the purposes of the present invention is to provide an injectable Ca-loaded 2+ -A method for preparing a nanocomposite material of tannic acid comprises the following steps:
[0008] (1) dissolving a certain amount of Ca(NO3)2·4H2O and tannic acid (TA) in deionized water, adjusting the pH value of the mixed solution to 7.4 with a 2M NaOH solution, heating the mixed solution for a period of time, and the color of the mixed solution changes from colorless and transparent to dark blue. The dark blue crude product is centrifuged, washed with deionized water, collected, and vacuum dried to obtain a CaTA nanocomposite material for later use;
[0009] (2) A certain amount of four-arm polyethylene glycol (PEG-OH4) and lipoic acid (LA) were dissolved in dichloromethane. Next, the system activated the carboxyl group of LA and catalyzed the esterification reaction: 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 4-dimethylaminopyridine (DMAP) were added, and stirring was continued at room temperature. After 24 hours, the mixed solution was concentrated by rotary evaporation, precipitated in ice ether, and vacuum dried to obtain pure PEG-SS4 for use;
[0010] (3) Injectable CaTA@Gel via Ca 2+ - Sodium alginate ion crosslinking and PEG-SS4 free radical polymerization under ultraviolet light: Sodium alginate (SA) and the PEG-SS4 are dissolved in deionized water, and the CaTA nanocomposite is added to form an injectable turbid liquid. The mixture is irradiated with ultraviolet light for free radical polymerization, and then placed in a fume hood for 1 hour to spontaneously form CaTA nanocomposite. 2+ -SA ion network to obtain CaTA@Gel.
[0011] Furthermore, in step (1), the mass ratio of the Ca(NO3)2·4H2O to the TA is 7:0.1-0.5, and the concentration of the Ca(NO3)2·4H2O in the deionized water is 17.5 g / L.
[0012] Furthermore, it is characterized in that in step (1), the heating is 50°C for 4 hours; the centrifugal speed is 8000 rpm, and the centrifugal time is 20 minutes; and the vacuum drying is 65°C for 24 hours.
[0013] Further, in step (2), the mass ratio of the PEG-OH4 to the LA is 5:1, and the PEG-OH 4与 The solid-liquid ratio in dichloromethane is 1 g:10 mL, and the mass ratio of the PEG-OH4, EDC·HCl and DMAP is 1:0.2:0.05.
[0014] Furthermore, in step (2), the evaporation concentration is carried out at a temperature of 40° C. for 10 min; and the vacuum drying is carried out at 65° C. for 12 h.
[0015] Furthermore, in step (3), the mass ratio of the sodium alginate to the PEG-SS4 is 1:20-50, the concentration of the PEG-SS4 in the deionized water is 0.3 mg / μL, and the mass ratio of the CaTA nanocomposite material to the PEG-SS4 is 1-5:9.
[0016] Furthermore, in step (3), the wavelength of the ultraviolet light is 365 nm, and the irradiation time is 3 to 5 minutes.
[0017] The technical concept of the present invention is: Ca 2+ -SA ion chelation increases the viscosity of the mixture to ensure that it can be retained at the lesion site after being injected into the periodontal pocket. Next, under ultraviolet irradiation, the disulfide bonds at the ends of PEG-SS4 are activated for free radical polymerization to form the final double network of CATA@Gel, which fixes it at the infection site and continuously releases CaTA.
[0018] The second object of the present invention is to provide an injectable Ca-loaded 2+ -Nanocomposite materials of tannic acid.
[0019] The third object of the present invention is to provide an injectable Ca-loaded 2+ -Application of tannic acid nanocomposites.
[0020] Further, the injectable loaded Ca 2+ -Tannic acid nanocomposites were injected in situ into periodontal defects.
[0021] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] (1) Multifunctional injectable CaTA@Gel for periodontitis treatment: The present invention discloses an injectable CaTA@Gel for periodontitis treatment, which has multiple functions. 2+ The double network formed by -SA ion reaction and free radical cross-linking can effectively deliver and release CaTA nanocomposites and create a suitable environment for alveolar bone regeneration.
[0023] (2) Both in vitro and in vivo data show that the injectable CaTA@Gel of the present invention has significant effects in antibacterial, scavenging reactive oxygen species (ROS) and osteogenesis. Finally, periodontitis was successfully treated, and the new tissue was similar to healthy tissue in appearance, structure and composition.
[0024] (3) The versatility and convenient use of the injectable CaTA@Gel of the present invention provide a practical strategy for the treatment of periodontitis and have great potential for future clinical transformation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 Characterization of CATA nanocomposites: (A) XPS spectrum of CaTA, (BD) high-resolution XPS spectra of Ca, O and C in CaTA, (E) XRD pattern of CaTA, (F) TGA curves of CaTA and TA, (G) SEM image of CaTA (scale bar is 200 nm), (H) TEM image of CaTA (scale bar is 10 nm), (I) size distribution of CaTA, data are mean ± standard deviation (n≥3).
[0027] Figure 2 Characterization of CaTA@Gel: (A) SA solution without cross-linked network, (B) with Ca 2+ -SA ionic network of CaTA / SA hydrogel, (C) Photograph of CaTA@Gel with double network, scale bar = 500 μm, (D) 2+ -Shear thinning of SA ion network and SA solution (SA solution as control group), (E, F) Ca 2+-Storage modulus (G') and loss modulus (G") of SA ion hydrogel and CaTA@Gel, (G, H) compression properties of CaTA@Gel, (I) release behavior of CaTA from CaTA@Gel, data are mean ± SD (n≥3), *p<0.05, **p<0.01.
[0028] Figure 3 Biocompatibility and antibacterial activity: (A) hemolysis test of CaTA nanocomposites with different concentrations, (B) relative optical density of the supernatant of each group, photos of blank groups and CaTA10@Gel supernatant against (C, D) Escherichia coli and (E, F) Staphylococcus aureus, antibacterial rates against (G) Escherichia coli and (H) Staphylococcus aureus, data are mean ± SD (n ≥ 3), *p < 0.05, **p < 0.01.
[0029] Figure 4 Figure 3 ROS scavenging and osteogenic ability of CaTA nanocomposites: (A) Absorption spectra of salicylic acid (SA) reacting with ·OH in the presence or absence of different concentrations of CaTA; (B) ·OH scavenging rate of CaTA; (C) ROS scavenging by ·O2 in the presence or absence of different concentrations of CaTA. - Absorption spectrum of reduced NBT; (D)·O2 of CaTA - Clearance rate; (E) Alkaline phosphatase (ALP) staining of bone marrow mesenchymal stem cells (BMSCs) co-cultured with osteogenic medium and different concentrations of CaTA; (F) Relative optical density values of ALP staining in different groups; (G I) Quantitative real-time polymerase chain reaction (RT-PCR) analysis of osteogenic genes (including BMP-2, ALP and osteocalcin (OCN)) after induced culture in CaTA@Gel, data are mean ± SD (n ≥ 3), *p < 0.05, **p < 0.01.
[0030] Figure 5 In vivo therapeutic effect of injectable CaTA@Gel in the treatment of periodontitis: (A) Schematic diagram of the construction of the rat periodontitis model induced by Porphyromonas gingivalis; (B) Gross observation photos of maxillary bones collected from different groups, the yellow arrows indicate the periodontal site, scale: 1 cm; (C) Three-dimensional reconstruction and vertical cross-sectional images of maxillary molars in different groups were performed by Micro-CT, the red line indicates the distance between ABC and CEJ, scale = 1 mm; (DF) Quantitative analysis of various alveolar bone parameters, data are mean ± SD (n ≥ 3), *p < 0.05, **p < 0.01.
[0031] Figure 6(A) Transverse sections of maxillary molars in different groups and (B) transverse sections of intermolar spaces in different groups obtained by Micro-CT, the red arrow indicates the distance between ABC and CEJ, scale = 1 mm. Quantitative analysis of alveolar bone (C) trabecular separation and (D) ABC-CEJ distance, data are mean ± SD (n ≥ 3), *p < 0.05, **p < 0.01.
[0032] Figure 7 Pathological analysis of each group of tissues. (A) H&E staining images of maxillary molars and intermolar spaces in different groups, (B) Masson staining images, (C) interleukin-6 (IL-6) and (D) tumor necrosis factor-α (TNF-α) immunohistochemical staining images of maxillary molars and intermolar spaces in different groups, scale bar = 500 μm.
[0033] Figure 8 FTIR spectra of TA (black) and CaTA (red).
[0034] Fig. 9 1H NMR spectra of PEG-OH4 (black) and PEG-SS4 (red).
[0035] Fig.10 (A) CaTA 30 / SA / PEG-SS4 ionic hydrogel and (B) CaTA 50 Photo of CaTA / SA / PEG-SS4 ionic hydrogel. (C) 30 / SA / PEG-SS4 ionic hydrogel, (D)CaTA 50 / SA / PEG-SS4 ionic hydrogel, (E)CaTA 30 @Gel and (F)CaTA 50 @Rheological properties of Gel.
[0036] Fig.11 (A) UV-visible spectra of CaTA at different concentrations, (B) CaTA concentration standard curve.
[0037] Fig.12 Schematic diagram of injectable CaTA@GEL for the treatment of periodontitis: (A) Preparation of injectable CaTA@GEL, (B) Ca 2+ -SA ion chelation and LA free radical cross-linking dual network, (C, D) Treatment and microenvironment of periodontitis in vivo. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The reagent sources of the present invention are:
[0040] Calcium nitrate tetrahydrate (Ca(NO3)2·4H2O), tannic acid (TA), 4-arm-polyethylene glycol (PEG-OH4), and sodium hydroxide (NaOH) were purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China).
[0041] 4-arm polyethylene glycol (PEG-OH4, MWCO = 8000Da), lipoic acid (LA), 4-dimethylaminopyridine (DMAP), and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) were purchased from Shanghai Meipu Co., Ltd.
[0042] Nitro blue tetrazolium (NBT), riboflavin, and methionine were obtained from Sigma-Aldrich.
[0043] Other chemicals were of analytical grade and were not used in the experiments without further purification.
[0044] Example 1 provides an injectable Ca-loaded 2+ -Nanocomposite materials of tannic acid.
[0045] (1) Dissolve 7 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and 216 mg of tannic acid (TA) in 400 mL of deionized water. Then, adjust the pH of the solution to 7.4 with 2 M sodium hydroxide solution, and then heat to 50°C and maintain for 4 hours. During the reaction, the color of the solution changes from colorless and transparent to dark blue. Collect the crude product by centrifugation at 8000 rpm for 20 min and wash with deionized water. Finally, vacuum dry at 65°C for 24 h to obtain the CaTA nanocomposite material.
[0046] (2) First, 1 g PEG-OH4 and 0.2 g LA were dissolved in 10 mL dichloromethane. Then, 0.2 g EDC·HCl and 0.05 g DMAP were added to the system to activate the carboxyl group of LA and catalyze the esterification reaction under continuous stirring at room temperature. After 24 h, the mixed solution was concentrated by rotary evaporation at 40 °C for 10 min and then precipitated in ice ether. Finally, pure PEG-SS4 was obtained by vacuum drying at 65 °C for 12 h.
[0047] (3) First, SA and PEG-SS4 were dissolved in deionized water. Next, CaTA nanocomposite was added to the above mixed solution to form an injectable turbid liquid. To further characterize the material, the mixture was injected into a cylindrical mold to gel. After injection, the sample was exposed to 365 nm UV light for 3 minutes for free radical polymerization. Afterwards, the sample was placed in a fume hood for 1 hour to allow CaTA to 2+ -SA ion network formed spontaneously.
[0048] The detailed ratios of CaTA@Gel are listed in Table S1:
[0049] Table S1: Detailed ratio of CaTA@Gel
[0050]
[0051] Preparation and characterization of CaTA and PEG-SS4:
[0052] To prepare CaTA@Gel, CaTA and PEG-SS4 were first prepared. TA is a natural polyphenol that can chelate with a variety of metal ions. Ca(NO3)2·4H2O can induce the oxidative coupling assembly of TA to form CaTA nanocomposites.
[0053] XPS spectra show the chemical composition and state of Ca in CaTA ( Figure 1 AD). The wide scan spectrum shows the presence of Ca, C, and O. The atomic ratio of Ca is 3.12%. At the same time, the high-resolution XPS spectrum shows that the Ca2p peak can be deconvoluted into two types: Ca 2p3 / 2 at 346.5 eV and Ca2p1 / 2 at 349.5 eV. The peaks at 531.1 eV and 532.8 eV in the O 1s spectrum may correspond to Ca-O and Ca-OH. The presence of Ca-O is due to the presence of Ca 2+ At the same time, the C 1s spectrum is fitted with three peaks: 284.5 eV, 285.6 eV and 287.6 eV, which are attributed to C=C, CO and C=O in TA, respectively. Figure 1 E shows the XRD pattern of CaTA, which shows many significant diffraction peaks, indicating that CaTA has a specific crystal structure.
[0054] In addition, FTIR analysis also proved that the fingerprint region of CaTA spectrum also showed corresponding peaks compared with pure TA, which proved that Ca 2+ Chelation between TA and Figure 6 ).exist Figure 1 In F, CaTA has better thermal stability than TA, and the TGA curve also shows that the Ca content in the CaTA nanocomposite is 18.51%, which verifies the thermal stability of TA and Ca2+ SEM and TEM images showed that the CaTA nanocomposite had a uniform spherical structure with a size of 247 ± 41.42 nm (Figure GI), which directly demonstrated the nanomorphology of CaTA.
[0055] exist Fig. 9 In the figure, it is obvious that there are characteristic peaks belonging to the PEG-OH4 repeating unit (peak e, -CH2) at 3.4-3.6ppm, while several new peaks appear in PEG-SS4. Peaks a and b (1.8 and 1.6ppm, -CH2) are the proton signals of the methylene in the LA carbon chain. Peaks c and d (2.4ppm and 2.1ppm, -CH2) belong to the methylene in the carbon chain and dithiolane ring, respectively. These characteristic peaks of LA indicate that PEG-SS4 was successfully synthesized.
[0056] Formation and characterization of CaTA@Gel:
[0057] CaTA@Gel is a kind of 2+ -SA ion coordination and dithiolane free radical polymerization of PEG-SS4. Figure 2 A and 2B show that the CaTA / SA / PEG-SS4 solution can remain coagulated even when the test tube is inverted, while the SA / PEG-SS4 solution obviously flows down under the same conditions, indicating the presence of Ca 2+ -SA chelation. In order to ensure the optimal ratio of CaTA@Gel, the injectability, coagulation time and gelation time were comprehensively investigated. Table S1 shows the orthogonal test of hydrogel ratio selection. We can see that under the same conditions, when the CaTA concentration increases, the coagulation time and gelation time are shortened. This is because high concentrations of CaTA can provide more Ca 2+ Chelate with SA, thereby accelerating ion coordination. In addition, due to the increase in the number of carboxyl groups, the increase in SA concentration will also reduce the coagulation and gelation time, making the chelation sites more concentrated. However, the ideal situation is to have a suitable operating window for injection and subsequent gelation, which means that the coagulation and gelation time cannot be too fast, otherwise the system cannot be injected. On the other hand, the coagulation and gelation time cannot be too slow, otherwise the double network cannot be formed after UV irradiation. Therefore, due to its injectability and gelation ability, 10, 30 and 50 mg CaTA were dissolved in 300 μL SA / PEG-SS4 solution (CaTA 10 / SA / PEG-SS4、CaTA 30 / SA / PEG-SS4 and CaTA 50 / SA / PEG-SS4) were used for further study of hydrogel characterization. Accordingly, after UV irradiation, these three samples were named CaTA 10 @Gel, CaTA30 @Gel and CaTA 50 @Gel( Figure 2 C).
[0058] Figure 2 D shows the shear thinning of SA / PEG-SS4 solutions containing 0, 10, 30, and 50 mg CaTA. It is clear that all samples have shear thinning properties. In the concentration-dependent channel of ion chelation, the viscosity increases with the addition of CaTA, with CaTA 50 / SA / PEG-SS4 showed the highest viscosity, which was expected in the orthogonal experiment. After complete ion chelation, the sample showed obvious gel properties. Figure 2 E and Fig.10 As shown in AD, CaTA 10 / SA / PEG-SS4、CaTA 30 / SA / PEG-SS4 and CaTA 50 / SA / PEG-SS4 all formed ionic hydrogels as a whole, and their storage modulus (G') was higher than the loss modulus (G"), showing elasticity. 10 / SA / PEG-SS4、CaTA 30 / SA / PEG-SS4 and CaTA 50 The G' of / SA / PEG-SS4 were 0.28 ± 0.024 kPa, 0.68 ± 0.104 kPa, and 0.66 ± 0.079 kPa, respectively, which indicated that more Ca 2+ The strength of the ionic network can be enhanced. After ultraviolet irradiation causes the PEG-SS4 free radicals to polymerize to form a double network, the elasticity of the hydrogel is enhanced ( Figure 2 F. Fig.10 E and F). The results showed that CaTA 10 @Gel, CaTA 30 @Gel and CaTA 50 The G' of CaTA50@Gel decreases with increasing CaTA concentration, reaching 12.0±0.97 kPa, 9.9±0.98 kPa, and 6.4±0.35 kPa, respectively. This seems to contradict the data of ionic hydrogels and is contrary to the inherent experience about the double network. In fact, due to the dark blue color of CaTA, excess CaTA will affect the efficiency of UV irradiation during the PEG-SS4 photocrosslinking process. Therefore, CaTA50@Gel shows the lowest G' among the samples.
[0059] To further characterize the mechanical properties, DMA tests were performed and the data showed that CaTA 10 The stress-strain curve of @Gel is the steepest, which means that among the three groups, CaTA 10@Gel can reach the maximum strain and withstand the highest stress ( Figure 2 G). Figure 2 H directly indicates CaTA 10 The compression modulus of @Gel is 29.9±0.67 kPa, while CaTA 30 @Gel and CaTA 50 The compression modulus of @Gel gradually decreased to 25.1±1.24 kPa and 10.0±2.22 kPa, respectively, which is consistent with their rheological behaviors. 10 @Gel via Ca 2+ -SA ion chelation and PEG-SS4 free radical cross-linking can form a stable and strong double network after injection and UV irradiation, which may be beneficial to the sustained release of CaTA and support osteogenesis.
[0060] The release curve of CaTA from CaTA@Gel was shown by the CaTA standard curve and the supernatant of CaTA@Gel in PBS ( Figure 2 I and Fig.11 ). The results showed that CaTA 10 @Gel released 78.3±7.45% in 14 days, which is comparable to CaTA 30 @Gel and CaTA 50 Compared with β-actin@Gel, the latter two showed a sustained release behavior, with a burst release of 74.9±6.12% and 80.1±6.93% after the first 24 h, respectively, indicating that the sustained release behavior was affected by the incomplete photocrosslinking caused by excessive CaTA. 2+ -The effect of SA ion chelation on CaTA release. 10 @Gel was used as a negative control. The results showed that CaTA without SA 10 @Gel also had a similar burst release of 72.4±3.44% after the first 24 hours, demonstrating that Ca 2+ -SA ion chelation actually facilitates sustained release.
[0061] CaTA was selected based on comprehensive considerations of injectability, gelation of ionic and free radical networks, mechanical properties, and CaTA release behavior. 10 @Gel for follow-up experiments.
[0062] Test 1: Biocompatibility and antimicrobial activity test
[0063] Since gingival bleeding and oral bacterial environment are characteristics of periodontitis, blood compatibility and antimicrobial activity tests were performed to ensure the biosafety of the CaTA nanocomposites.
[0064] Hemolysis test: Fresh blood from rats was centrifuged (1500r / min, 15min) and gently washed to obtain red blood cells (RBCs), and then mixed with 0.1M PBS. Next, 100μL of red blood cell solution was added to 1.5mL of PBS containing different concentrations of CaTA (250, 500 and 800μg / mL). In addition, 100μL of red blood cell solution was mixed with 1.5mL of deionized water and PBS, respectively, as positive and negative controls. After incubation at 37°C for 3 hours, the samples were photographed and recorded, and the supernatant was collected (1500r / min, 15min), and the absorbance at 540nm was measured by an enzyme reader to analyze the blood compatibility of CaTA.
[0065] Antibacterial activity of CaTA: Staphylococcus aureus (S. aureus, Gram-positive bacteria) and Escherichia coli (E. coli, Gram-negative bacteria) were selected as models to determine the antibacterial activity of CaTA by plate colony counting method. CaTA (1 mg / mL) was mixed with 1 mL of bacterial solution (10 6 CFU / mL) at 37°C. After 24 hours, the mixed solution was diluted, spread and co-cultured for another 18 hours. The culture dish was photographed and the antibacterial rate was calculated by the following formula:
[0066] Antibacterial rate (%) = (N0-N1) / N0×100%
[0067] Here, N0 is the number of bacteria without CaTA, and N1 is the number of bacteria with CaTA.
[0068] Figure 3 A shows that after centrifugation, the red blood cells in PBS and CaTA solutions can remain aggregated, and the relative optical density values of CaTA solutions of different concentrations are close to those of PBS ( Figure 3 B), which indicates that CaTA has good blood compatibility compared with deionized water.
[0069] Tannic acid (TA) is reported to be an important component of the chemical defense system of plants against pathogen invasion and insect attack. Therefore, it is often used as a preservative and antimicrobial agent in the food and medical industries. Here, the number of Escherichia coli and Staphylococcus aureus was significantly inhibited by the plate colony count method ( Figure 3 CF). The antibacterial rates of CaTA against Escherichia coli and Staphylococcus aureus were 99.3±8.25% and 98.7±5.17%, respectively ( Figure 3 G and H), demonstrating that CaTA has good antibacterial activity. These results imply that CaTA@Gel may have good biocompatibility and antibacterial activity in the treatment of periodontitis.
[0070] Experiment 2: Reactive oxygen species (ROS) scavenging ability of CaTA nanocomposites
[0071] The scavenging efficiency of CaTA on ·OH in vitro was determined by detecting the amount of ·OH in salicylic acid. First, ferrous sulfate (FeSO4, 2×10 -4 M) was added to hydrogen peroxide (H2O2, 2×10 -4 M) to produce ·OH through the Fenton reaction. Next, different concentrations (0, 1.25, 2.5, 5, 10, 25, 50, and 100 μg / mL) of CaTA were introduced into the above solution to remove ·OH. Finally, salicylic acid (1×10 -3 M) detects the remaining ·OH, which can oxidize salicylic acid to purple 2,3-dihydroxybenzoic acid. Its absorption peak (510nm) is recorded by UV spectrometer. The ·OH removal rate is calculated by the following formula:
[0072] OH removal rate (%) = (A0-A1) / (A0-A s )×100%
[0073] Where A0 is the absorbance of 2,3-dihydroxybenzoic acid without CaTA, A1 is the absorbance of 2,3-dihydroxybenzoic acid with CaTA, and A s is the absorbance of salicylic acid.
[0074] The inhibitory efficiency of CaTA on in vitro O2 - Briefly, riboflavin (20 μM), methionine (15 μM), NBT (75 μM), and CaTA (1.25, 2.5, 5, 10, 25, 50, and 100 μg / mL) were dissolved together in 0.1 M PBS. Afterwards, the mixture was exposed to UV light for 15 min to allow ·O2 - Reduced NBT, the solution turns blue. The absorption peak at 560nm is quantified by UV spectrometer. Mixed solutions with and without UV irradiation are used as positive and negative controls, respectively. ·O2 - The inhibition rate was calculated by the following formula:
[0075] O2 - Inhibition rate (%) = (A p -A1) / (A p -A n )×100%
[0076] Among them, A p and A n are the absorbance of the positive control and negative control, respectively, and A1 is the absorbance of the treated sample.
[0077] Although ROS are a product of normal metabolism, excessive ROS can break the balance with the antioxidant stress system, induce a pathological environment, and accelerate the development of periodontitis. Figure 4 As shown in Figure 4, since the polyphenol structure of CaTA nanocomposites can directly react with and neutralize ROS, it can not only significantly scavenge ·OH but also ·O2 - .
[0078] The ·OH scavenging rate was obtained by measuring the absorption intensity of 2,3-dihydroxybenzoic acid (the product of salicylic acid oxidation by ·OH). It is obvious that the absorption peak at 510 nm decreased in a CaTA concentration-dependent manner ( Figure 4 A). When the CaTA concentration was 100 μg / mL, about 59.6±2.99% of ·OH could be removed ( Figure 4 B), showing excellent ·OH scavenging ability.
[0079] Similarly, by measuring the amount of O2 - The absorption intensity of the blue methylhydrazone produced by reducing NBT is used to obtain O2 - Clearance rate. Figure 4 C shows that the absorbance at 560nm decreases at different CaTA concentrations. 100μg / mL CaTA can inhibit more than 60% of ·O2 - ( Figure 4 D). These results confirm that CaTA nanocomposites have excellent ROS scavenging ability in the periodontitis environment.
[0080] Experiment 3: In vitro osteogenic capacity
[0081] Bone marrow mesenchymal stem cells (BMSCs) from SD rats were cultured at 5×10 3The cells were seeded into 96-well plates at a density of 10 cells and cultured with standard culture medium at 37°C for 24 hours. Then, the culture medium was replaced with osteogenic culture medium containing CaTA nanocomposites (25, 50 and 100 μg / mL) and co-cultured with BMSCs at 37°C for 7 days. The group using standard culture medium was a negative control, and the group using only osteogenic culture medium (CaTA 0 μg / mL) was a positive control. During osteogenic induction, the culture medium was changed every day. After 7 days, the cells were fixed with 4% paraformaldehyde solution, washed 3 times with PBS, and stained with 0.1% (alkaline phosphatase) ALP staining kit at 37°C for 30 minutes. After staining, BMSCs were washed several times with PBS to remove excess dye. 100 μL of 10% SDS solution was added to each well, and the cells were lysed at 37°C for 1 hour to release ALP. Finally, the optical density value of each well was read at 520 nm using a microplate reader (SpectraMaxM2, Molecular Instruments, USA).
[0082] In addition, BMSCs were seeded into freeze-dried porous CaTA@Gel, and osteogenic genes were measured after induction. BMSCs seeded into freeze-dried porous hydrogels without CaTA were used as a control group. Briefly, the hydrogels loaded with BMSCs were cultured with osteogenic medium at 37°C for 7 and 14 days. The cells were collected at the preset time, and the expression levels of osteogenic genes including BMP-2, ALP and OCN were evaluated by real-time quantitative polymerase chain reaction (qRT-PCR, CFX96, Bio-Rad, USA). The primer information is listed in Table S2.
[0083] Table S2 Primer information
[0084]
[0085] Bone regeneration is essential in the treatment of periodontal defects. Therefore, the osteogenic effect of bone marrow mesenchymal stem cells (BMSCs) in CaTA@Gel was verified by ALP staining and osteogenic gene expression levels. ALP is a typical biomarker of osteogenic differentiation and plays an important role in mineralization and bone regeneration. Figure 4 In E, in osteogenic medium (under induction conditions), the color of ALP staining was significantly enhanced and further deepened with the increase of CaTA concentration. In osteogenic medium containing 100 μg / mL CaTA, the relative optical density value of ALP staining was the highest among all samples ( Figure 4 F) Ca 2+ Ca plays a central role in the entire life cycle from bone formation to repair. 2+ levels were associated with enhanced osteoblast activity and mineralization. Here, CaTA nanocomposites continuously produced Ca 2+ , constructing a high Ca 2+The extracellular environment of CaTA@Gels promoted the osteogenic activity of BMSCs. In addition, compared with osteogenic medium alone, the expression of osteogenic genes (including BMP-2, ALP, and OCN) by BMSCs in CaTA@Gels increased significantly after 14 days ( Figure 4 GI). Therefore, it is reasonable to conclude that CaTA nanocomposites and CaTA@Gels possess osteogenic properties.
[0086] Experiment 4: In vivo therapeutic effect of injectable CaTA@Gel in the treatment of periodontitis
[0087] To evaluate the therapeutic effect of injectable CaTA@Gel in periodontitis, a typical bacterial-induced periodontitis model in SD rats was established. First, 25 male SD rats (6-8 weeks old, 220-250 g, n = 5) were randomly divided into 5 groups: (1) healthy rats without periodontitis (healthy group); (2) rats with periodontitis treated with PBS only (blank group); (3) rats with periodontitis treated with SA and PEG-SS4 only (gel group); (4) rats with periodontitis treated with CaTA solution only (CaTA group); (5) rats with periodontitis treated with CaTA@Gel (CaTA@Gel group). The left maxillary second molars of the rats were ligated with 4-0 silk thread, and then Porphyromonas gingivalis (10 9 CFU / mL, 500μL) once, and drank high sugar water (100g / L glucose). After 14 days, 200μL PBS, SA / PEG-SS4 solution, CaTA solution, and CaTA / SA / PEG-SS4 solution were injected into the periodontal pocket, respectively. For the gel group and CaTA@Gel group, SA / PEG-SS4 solution and CaTA / SA / PEG-SS4 solution required ultraviolet irradiation for 5 minutes to gel. After 4 weeks, the complete maxilla was obtained from the sacrificed rats, and the gross observations were recorded by photographing. Micro-computed tomography (Micro-CT) analysis, hematoxylin-eosin (H&E) staining, Masson staining, and immunohistochemical staining were further performed to evaluate the in vivo treatment effects of periodontitis, including alveolar bone regeneration and inflammation inhibition.
[0088] The potential of injectable CaTA@Gel to support new tissue deposition was evaluated in a bacterial-induced rat periodontitis model. Figure 5 A).
[0089] First, it is obvious from macroscopic observation that the periodontal defect treated with CaTA@Gel injection has the best therapeutic effect and is closest to the appearance of healthy maxillary bones, that is, the maxillary molars are closely arranged, and there are no visible cavities and hyperplastic tissues between the molars (yellow arrows). Figure 5B. In addition, it can be more clearly seen through three-dimensional reconstruction and vertical cross-sectional images that the CaTA@Gel group promoted alveolar bone regeneration, reduced the distance between the alveolar ridge crest (ABC) and the cementoenamel junction (CEJ) and the gap between the maxillary molars, which is consistent with the healthy group ( Figure 5 C) In addition, Figure 5 In DF, the bone volume fraction (BV / TV), trabecular thickness (Tb.Th), and trabecular number (Tb.N) of the CaTA@Gel group were the highest among all periodontitis model treatment groups, while these indicators of the blank group were the lowest, indicating that the periodontitis model was successfully established and CaTA@Gel indeed promoted osteogenesis.
[0090] For a more intuitive look, the cross-sectional images of the maxillary molars and the cavities caused by periodontitis were recorded. Figure 6 In A, alveolar bone loss was significant in the blank group, gel group, and CaTA group. The distance between CEJ and ABC was large, while the reduction of CEJ-ABC distance in the CaTA@Gel group indicated complete alveolar bone regeneration, which was comparable to the healthy group. At the same time, the cross-sectional image of the intermolar space also showed that there were no teeth above the target area due to the large intermolar distance ( Figure 6 B). In contrast, there is a clear white shadow in the upper left corner of the images of the healthy group and the CaTA@Gel group, which is the cross-section of the tooth, indicating that the molars are closely arranged without obvious cavities caused by alveolar bone loss. Figure 6 C shows that the trabecular separation (Tb.Sp) of the CaTA@Gel group decreased sharply, which means that bone resorption was inhibited and new tissue was successfully reconstructed. The CEJ-ABC distance of the CaTA@Gel group was 0.56±0.047mm, which was similar to 0.50±0.043mm of the healthy group and was the shortest among the four periodontitis model groups ( Figure 6 D).
[0091] In addition, hematoxylin-eosin (H&E) staining and Masson staining images showed that there was no obvious alveolar bone resorption in the CaTA@Gel group and the healthy group. However, in the blank group, gel group, and CaTA group, not only was the alveolar bone height greatly reduced, but the gap between the molars was significantly increased, which are typical symptoms of periodontitis. At the same time, Masson staining also showed that most of the new tissue in the CaTA@Gel group was mature bone tissue, which was similar to that in the healthy group ( Figure 7 A and B).
[0092] At the same time, the microstructure of the tissue also indicated the degradation of the gel and CaTA@Gel, as no material remained in the tissue. Due to the esterification reaction between lipoic acid (LA) and four-arm polyethylene glycol (4-armPEG), hydrolysis leads to the collapse of the PEG-SS4 network. On the other hand, according to relevant reports, the hydrogel enters the degradation stage after expanding to the limit, and the density of its structure gradually decreases until it finally decomposes. Immunohistochemistry results showed that the expression levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in the blank group were significantly higher than those in the healthy group, and this situation could also be observed in the gel group and CaTA group, indicating that there was an inflammatory environment in the blank group, gel group and CaTA group. However, in the CaTA@Gel group, the expression levels of these two factors were significantly reduced, similar to the levels in healthy tissues ( Figure 7 C and D).
[0093] Based on the above results, it is reasonable to speculate that the therapeutic effect of injectable CaTA@Gel may be related to the following factors: (1) CaTA@Gel can be injected into the periodontal defect in situ and gelled to facilitate the sustained release of CaTA nanocomposites. (2) CaTA@Gel can inhibit oral bacteria and remove reactive oxygen species (ROS), thereby alleviating the inflammatory environment. (3) The Ca in CaTA@Gel 2+ It can promote the osteogenesis of bone marrow mesenchymal stem cells (BMSCs) in situ, thereby regenerating alveolar bone. All these reasons improve the treatment effect of periodontitis.
[0094] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: The following steps are involved: (1) dissolving a certain amount of Ca(NO3)2·4H2O and TA in deionized water, adjusting the pH of the mixed solution to 7.4 with a NaOH solution, heating for a period of time, centrifuging, washing, collecting, and vacuum drying the crude product to obtain a CaTA nanocomposite material for later use; (2) Dissolve a certain amount of PEG-OH4 and LA in dichloromethane, add EDC·HCl and DMAP, and continue stirring at room temperature. After 24 hours, evaporate and concentrate, precipitate in ice ether, and vacuum dry to obtain PEG-SS4 for later use; (3) Sodium alginate and the PEG-SS4 are dissolved in deionized water, the CaTA nanocomposite material is added, the mixture is irradiated with ultraviolet light, and then placed in a fume hood for 1 hour to obtain CaTA@Gel.
2. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (1), the mass ratio of the Ca(NO3)2·4H2O to the TA is 7:0.1-0.5, the concentration of the Ca(NO3)2·4H2O in the deionized water is 17.5 g / L, and the concentration of the NaOH solution is 2M.
3. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (1), the heating is performed at 50° C. for 4 h; the centrifugal speed is 8000 rpm, and the centrifugal time is 20 min; and the vacuum drying is performed at 65° C. for 24 h.
4. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (2), the mass ratio of the PEG-OH4 to the LA is 5:1, the solid-liquid ratio of the PEG-OH4 to dichloromethane is 1 g:10 mL, and the mass ratio of the PEG-OH4, EDC·HCl and DMAP is 1:0.2:0.
05.
5. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (2), the evaporation concentration is carried out at a temperature of 40° C. for 10 min; and the vacuum drying is carried out at 65° C. for 12 h.
6. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (3), the mass ratio of the sodium alginate to the PEG-SS4 is 1:20-50, the concentration of the PEG-SS4 in the deionized water is 0.3 mg / μL, and the mass ratio of the CaTA nanocomposite material to the PEG-SS4 is 1-5:
9.
7. An injectable Ca-loaded 2+ - A method for preparing a nanocomposite material of tannic acid, characterized in that: In step (3), the wavelength of the ultraviolet light is 365 nm, and the irradiation time is 3 to 5 minutes.
8. An injectable Ca-loaded 2+ - A nanocomposite material of tannic acid, characterized in that The injectable loaded Ca obtained by the preparation method according to any one of claims 1 to 7 2+ -Nanocomposite materials of tannic acid.
9. An injectable Ca-loaded 2+ - Application of a nanocomposite material of tannic acid, characterized in that The injectable loaded Ca as claimed in claim 8 2+ -Tannic acid nanocomposites for the treatment of periodontitis.
10. The injectable loaded Ca according to claim 9 2+ - Application of a nanocomposite material of tannic acid, characterized in that The injectable Ca-loaded 2+ -Tannic acid nanocomposites were injected in situ into periodontal defects.